Ruang Terbuka Hijau Di Bantaran Sungai Bengawan Solo(Restorasi Bandar Bengawan Solo) - Afif, Rifyal; , Dr. Ir. Qomarun, MM; , Wisnu Setiawan, ST., M.Arch.,Ph.D (2016)
The existence of RTH in Surakarta driven by accelerating growth over the land did not awaken into undeveloped land, especially over the function as a non-green building. While according to Regulation of the Minister of Public Works No. 05 of 2008 requires that public green open space urban areas the minimum must be met by 20% of the total area of the city, Also mentioned also in Law No. 26 years 2007.Ruang Green Open Surakarta City still does not meet only 18% whereas the need for green space the city is 30% to meet the 12% longer then made the green space on the banks of the Bengawan Solo river. Green Open Space in Bengawan Solo River Plate is the land acquisition of informal settlements or slums around the banks of the Bengawan Solo river. Bengawan Solo river banks inhabited by many illegal settlements or slums, the government program Surakarta mentertibkan the riverbank area of informal settlements or slums. The government program for the functioning of the Solo area as a green open space in order to meet the criteria of Green Open Space City to 30%.